2017
DOI: 10.1371/journal.pone.0175016
|View full text |Cite
|
Sign up to set email alerts
|

OAZ1 knockdown enhances viability and inhibits ER and LHR transcriptions of granulosa cells in geese

Abstract: An increasing number of studies suggest that ornithine decarboxylase antizyme 1 (OAZ1), which is regarded as a tumor suppressor gene, regulates follicular development, ovulation, and steroidogenesis. The granulosa cells in the ovary play a critical role in these ovarian functions. However, the action of OAZ1 mediating physiological functions of granulosa cells is obscure. OAZ1 knockdown in granulosa cells of geese was carried out in the current study. The effect of OAZ1 knockdown on polyamine metabolism, cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Polyamine contents were measured by HPLC using an Agilent 1100 Series system (Agilent Technologies, CA, USA) following a benzoylation procedure as described previously [ 18 ]. A 20 µL of benzoyl polyamines were separated on a 5 μm particle size C18, 4.6 × 250 mm column (Agilent Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Polyamine contents were measured by HPLC using an Agilent 1100 Series system (Agilent Technologies, CA, USA) following a benzoylation procedure as described previously [ 18 ]. A 20 µL of benzoyl polyamines were separated on a 5 μm particle size C18, 4.6 × 250 mm column (Agilent Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Female laying geese at the age of 7 months were killed by cervical dislocation. Follicle tissues and primary granulosa cells were quickly removed and processed as previously described [ 8 , 22 ]. In brief, granulosa cells were cultured in a DMEM/F12 medium supplemented with 3.0% FBS and 100 U/ml of penicillin/streptomycin in a humidified incubator at 37°C and 5.0% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have suggested that numerous ROS are produced by the ovaries in female animals during folliculogenesis and ovulation [ 5 , 6 ]. Granulosa cells, which surround oocytes in ovaries, play a pivotal role in follicular development, ovulation, atresia and steroidogenesis [ 7 , 8 ]. It is well known that oxidative stress induces granulosa cell apoptosis, which plays a vital role in initiating follicular atresia [ 9–11 ].…”
Section: Introductionmentioning
confidence: 99%
“…), whereas the OAZ1 ( ornithine decarboxylase antizyme 1 ) gene inhibits this process (Kang et al . ).…”
Section: Introductionmentioning
confidence: 97%